Avaliação do potencial da espécie Vetiveria Zizanioides na fitorremediação de metais-traço presentes em ambientes aquáticos - Edilene Aparecida Peixoto e Almeida (2011)
Phytoremediation is an emerging technology that can be considered an innovative and low cost alternative compared to other remediation technologies. In aquatic environments, it can be considered a polishing of the infected matrix, showing efficient potential for reducing the contaminants present in the water. The use of plants as a mechanism to degrade, extract or immobilize contaminants is an economically viable and very effective strategy. In this study we evaluated the potential of the species Vetiveria zizanioides in phytoremediation of trace metals such as cadmium, lead, chromium, nickel and zinc present in the water. The plants were subjected to concentrations of these elements in solution and their tolerance, as well as their potential for sorption, was evaluated in two steps of concentrations or campaigns. In the first campaign of the experimental trials, the plants were subjected to concentrations of trace metals approximate to the maximum allowed for effluent discharge, defined by CONAMA Resolution No. 357 from 2005. In the second campaign of the experimental trial, the administered concentrations were ten times the initial concentration referring to the elements Cr, Ni and Zn, twenty times that of Pb and thirty times the initial administered concentration of the element Cd. The criterion used for obtaining the concentrations regarding the second campaign was only a practical matter, to facilitate the measurements in the test tube in the field. For the development of the methodology, Vetiver grass was grown using the hydroponic technique, in which the roots were submerged in water contaminated with the trace elements relevant to our project. The species Vetiveria zizanioides showed tolerance to contamination and an effective potential in the removal of the trace metals present in the water. The results indicate the potential of the species as a promising candidate for use in phytoremediation programs in aquatic environments.